See the dog : three stories about a cat - LaRochelle, David (Candlewick Press, 2021)
"Max the dog is sick today, but have no fear - Baby Cakes the cat is happy to take his place! But when the book tells her to dig a hole, fetch a stick, and guard the sheep, the cat responds in very un-doglike ways" -- Back cover.